IMPLEMENTATION OF CHARACTER EDUCATION IN HISTORY LEARNING IN HIGH SCHOOL - Rahman, Kholilur; Eka Rahayu; Medani P. Bhandari (Madani : Journal of Social Sciences and Social Science Education, 2023)
Character education in schools, both formal and non-formal, especially inMadrasas, is considered important. However, its implementation has not been fullyrealized in the field. The aim of this research is to determine the application ofcharacter education in history learning. This research uses a qualitative methodwith a descriptive approach, the data collection techniques used by researchers inthis research are observation, and documentation. Data analysis techniques usingdomain data analysis. The research results show that character education has beenimplemented by history teachers. The implementation of character education inhistory learning at school aims to shape student character. Among the character values listed include love for Allah SWT, discipline, mutualcooperation.